2013
DOI: 10.1177/0194599813495815a23
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Safety of the Submental Flap for Reconstruction in Oral Cavity Malignancies

Abstract: Objectives: 1) Recognize the submental flap as an excellent option for oral cavity reconstruction. 2) Evaluate the oncologic safety of the submental flap given transposition of potentially involved nodal basins to the reconstruction site. Methods: Retrospective chart review of submental flap reconstructions for oral cavity defects secondary to cancer resections performed at a tertiary referral center between 2001 and 2012. Analysis included tumor location, staging, reconstructive details, postoperative course,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Furthermore, Kaplan‐Meier curves examining recurrence also failed to demonstrate difference between the two groups of patients. Although other published studies have suggested the oncologic safety of the SIPF, the current study is uniquely poised to make this statement based on its patient population size and inclusion of a comparative control group . This is the best evidence to date that demonstrates SIPF does not compromise oncologic results when performed in the setting of head and neck malignancy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Kaplan‐Meier curves examining recurrence also failed to demonstrate difference between the two groups of patients. Although other published studies have suggested the oncologic safety of the SIPF, the current study is uniquely poised to make this statement based on its patient population size and inclusion of a comparative control group . This is the best evidence to date that demonstrates SIPF does not compromise oncologic results when performed in the setting of head and neck malignancy.…”
Section: Discussionmentioning
confidence: 95%
“…Hypothetically, if microscopic disease in level IA is transferred to the recipient site, this would grow and ultimately manifest as a local recurrence deep to the flap in the resection bed. Past series of SIPF patients have not demonstrated an elevated rate of local recurrence, although this has not been examined closely in a controlled study …”
Section: Introductionmentioning
confidence: 95%
“…Some evidence suggests that this can be done. When a submental flap is used for oncologic reconstruction, dissection of the lymph nodes of level I can be performed while preserving the vascular pedicle from the facial vessels without compromising oncologic outcome, suggesting that facial vessels can be safely preserved. Furthermore, when the preglandular, postglandular, and prevascular nodes have been removed from sublevel IB, no additional nodes were found with the SMG specimen, suggesting that the SMG can be preserved while achieving the goal of the neck dissection .…”
Section: Discussionmentioning
confidence: 99%
“…One of the debated aspects of submental flap is its oncological safety. A cohort of 55 patients with squamous cell carcinoma of oral cavity in which submental flap was used for reconstruction was studied retrospectively by Howard et al 11 No recurrence was found intra-orally at the site of reconstruction, even though 10% of the cases had occult metastasis found at level 1. Use of the SIF may be complicated if the neck dissection is planned in addition to the surgical resection of the primary site.…”
Section: Discussionmentioning
confidence: 99%